PENENTUAN MODEL DAN UKURAN KINERJA PROSES ANTRIAN PADA UNIT PELAYANAN TEKNIK DINAS PUSKESMAS LIMBANGAN KABUPATEN KENDAL - Fatkhan Arissetya; Sugito Sugito; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
The UPTD (Unit Pelayanan Teknik Dinas) of Local Government Clinic of Limbangan in Kendal Regency is the only health-service in Limbangan Sub-district although there is another health-service such as doctors and midwifes. Since there are many people coming to the Local Clinic of Limbangan, it causes quite long queue. Therefore, it is needed to analyze the queuing model to finding out the system of the activity measure, so it can be concluded the queuing description and the service. If the distributrion of the arrival or the service is poisson or exponential, so the model is Markovial (M). However, if the distribution is not poisson or exponential, so the model is General (G). The queuing model of outpatients includes Regristrtion-Counter (M/G/1):(GD/∞/∞) , Medical Service (M/M/3):(GD/∞/∞) and Medicine-Counter (M/G/1):(GD/∞/∞). Meanwhile, the queuing model of hospitalized patients covers Hospitalized Rooms (M/M/16):(GD/∞/∞) and Payment Counter (M/G/1):(GD/∞/∞). It has been found out the best queue from the analysis in UPTD Local Government Clinic of Limbangan that is registration counter because the service time is quick and there are few queuing patients, so it won’t be hoarding